Precocious puberty in patients with Pompe disease - Tsai, Meng-Ju Melody; Chen, Mei-Huei; Chien, Yin-Hsiu; Tung, Yi-Ching (Frontiers in Endocrinology, 2023)
Introduction: The life expectancy of Pompe disease patients has increased due to improved neonatal screening and enzyme replacement therapy. Nevertheless, the potential effect of frequent medical device exposure on pubertal development in these patients is not well understood, so further investigation is warranted. Methods: In this cross-sectional study, we assessed the growth and puberty of nine Pompe disease patients. In addition, to determine the effects of frequent plastic medical device exposure in these patients, we measured urinary phthalate metabolites before and one day after enzyme replacement therapy. Results: Five out of nine patients (55%) with Pompe disease on enzyme replacement therapy had precocious puberty. Patients with precocious puberty had significantly shorter predicted adult heights compared to those with normal puberty (p = 0.014). The levels of mono-2-ethylhexyl phthalate (MEHP) and mono(2-ethyl-5-carboxypentyl) phthalate (MECPP) increased after enzyme replacement therapy, but the average levels of phthalate metabolites did not significantly differ between patients with normal and precocious puberty. Conclusion: Pompe disease patients on enzyme replacement therapy tend to have precocious puberty, which may reduce their adult height. There are no significant differences in urinary phthalate metabolites between normal and precocious puberty patients. Regular follow-up of growth and puberty in Pompe disease patients is important to improve their health outcomes.